Brain signal changes of the amygdala cortex according to the physical performance of fabric. Issue 3 (February 2023) - Yuan, Jie; Wang, Qicai; Shang, Shanshan; Lei, Yutian; Lou, Lin
The physical properties of fabric causing an uncomfortable tactile perception under certain clothing pressure has always been a difficult problem in the field of fabric comfort research. According to a large number of works in the literature, the amygdala was recognized as the key brain region for negative perceived emotions. In order to investigate the fabric factors causing the signal changes in the amygdala brain region, functional magnetic resonance imaging was used to monitor the amygdala brain region and its anatomical sub-brain region under the same degree of compression stimulation from several different corsets, and the percent signal changes (PSCs) were extracted and analyzed. The results showed that there was a significant positive correlation between the PSCs of the centromedial group of the amygdala and the average dynamic friction coefficient (MIU) of the fabric at the level of 0.05, and a general linear model was established ( R 2 = 0.998, p = 0.019). These results indicated that the surface friction properties of the fabric successfully attracted the attention of the central amygdala, and the attention increased linearly with the increase of MIU. This finding not only laid a foundation for exploring the brain perception mechanism of fabric discomfort, but also provides a possibility for further quantification of fabric discomfort perception by using the amygdala brain region.